Minority Victim Neglect and the Case Processing of Firearm Crimes - Vaughn, Paige E. (Victims & offenders, 2023)
Studies find mixed results regarding the effects of race on criminal justice case processing, likely because they rarely account for the race of both the victim and offender, and few consider how prosecutorial case screening may influence later criminal justice stages. This study examines the impact of victim and defendant race on case screening, bail, and sentencing outcomes for 1,131 firearm offenses that occurred between 2015 and 2018 in St. Louis, MO. Regressions modeling the relationships between each outcome and victim and defendant race (estimated separately and as defendant-victim racial dyads) find that cases involving Black victims, alone and in combination with Black defendants, are more likely than others to be dismissed by prosecutors during case screening, whereas legally relevant factors affect bail and sentencing outcomes. The results suggest that disregarding initial gatekeeping stages of criminal justice case processing may lead to the mistaken conclusion that racial disparities do not exist.